Bottom-up Budgeting FY 2015 Assessment: Camarines Sur - Joyce Anne Maramot; Donald B. Yasay; Reinier de Guzman (Philippine Institute for Development Studies (PIDS), 2015)
Bottom-up budgeting (BUB) is an adaptation of the participatory budgeting model in identifying and providing solutions to poverty at the municipal/city level. Leaders of civil society organizations engage with LGU officials in formulating a poverty alleviation plan to be considered in preparing the budget of national agencies the following fiscal year. This paper reports on how the guideline was implemented in three municipalities in Camarines Sur. The study then presents suggestions and recommendations to improve future project planning and monitoring.
Keywords: 330; Philippines; local governance; poverty alleviation; budget reform; Camarines Sur; participatory budgeting